A personal retrospective on language workbenches - van den Brand, Mark (Software and systems modeling, 2023)
Model-driven software engineering and specifically domain-specific languages have contributed to improve the quality of software and the efficiency in the development of software. However, the design and implementation of domain-specific languages requires still an enormous investment. Language workbenches are the most important tools in the field of software language engineering. The introduction of language workbenches has alleviated partly the development effort, but there are still a few major challenges that need to be tackled. This paper presents a personal perspective on the development of tools for language engineering and language workbenches in particular and future challenges to be tackled.